Rapid campimetry - a novel robust kinetic approach for visual field screening in glaucoma - Al-Nosairy, Khaldoon O.; Rodenbeck, Katharina; Vorholt, Sophie; Djouoma, Nidele; Thieme, Hagen; Müller, Fabian; Hoffmann, Michael B. (Frontiers in Medicine, 2024)
Purpose: To investigate the robustness and variability of a novel kinetic visual field (VF) screening method termed rapid campimetry (RC).In RC, a kinetic based perimeter, VF screening is enabled via kinetic-based testing on any computer (10°/4.7s at 40-cm viewing distance) and high contrast in dark room (1 cd/cm 2 ). In experiment 1): 30 participants [20 healthy participants (HC), 5 glaucoma patients (GLA) and 5 patients with cataract (CAT)] were included to test the intra-session variability (fatigue effect) and the following effects on RC: room illumination (140 cd/m 2 ), ±3 D refractive errors, media opacity. In experiment 2): Inter-session variability (1-3 weeks apart) was assessed in 10 HC and 10 GLA. Since RC detects absolute scotomas, the outcome measure was the size of physiological (blindspot) and pathological (glaucoma) scotomas in degrees. A repeated measures ANOVA was employed in experiment 1 and intraclass correlation (ICC) in experiment 2.Results: Neither the size of the blindspot nor the VF defects differed significantly between the different testing conditions. For intra-session variability, the average bias of blindspot size was -0.6° ± 2.5°, limits of agreement (LOA), in comparison to 0.3 ° ± 1.5° for VF defects, both with ICC of 0.86 and 0.93, respectively. For the inter-session repeatability, the average bias and LOA for blindspot size was 0.2° ± 3.85° in comparison 1.6° ± 3.1° for VF defects, both with ICC of 0.87 and 0.91, respectively.RC was robust to suboptimal testing VF conditions and showed good-to-excellent reliability between VF testing visits holding high potential for teleophthalmology.